2010
DOI: 10.4314/gjpas.v16i2.62832
|View full text |Cite
|
Sign up to set email alerts
|

Performance of maize (<i>Zea mays</i> l.) in crude oil treatment

Abstract: The performance of maize (Zea mays) in crude oil treatment was investigated at the University of Port Harcourt botanical garden. Germination and growth responses of Z. mays were examined using various crude oil pollution treatments. There was no significant difference in the germination and development of Z. mays subjected to oiling at 1-3% compared to those of the control (0%), while 4-5% oiling showed a significant difference at P=0.05. Percentage germination decreased with increase in concentration of crude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…The interaction between land and light oil spillage indicated that a unit of light crude oil spillage on farmland resulted in a proportionate decrease in crops output of 1.027 units and was statistically significant at 5%. These results obtained in these relationships confirmed that crude oil spillage on farm land had detrimental effects on crops production in Rivers State, Nigeria and affirmed that crude oil spillage reduces land productivity (Ekundayo et al, 2001;Saier, 2006;Okonwu et al;.…”
Section: Interaction Across Physical Inputs and Crude Oil Pollution Vsupporting
confidence: 58%
See 4 more Smart Citations
“…The interaction between land and light oil spillage indicated that a unit of light crude oil spillage on farmland resulted in a proportionate decrease in crops output of 1.027 units and was statistically significant at 5%. These results obtained in these relationships confirmed that crude oil spillage on farm land had detrimental effects on crops production in Rivers State, Nigeria and affirmed that crude oil spillage reduces land productivity (Ekundayo et al, 2001;Saier, 2006;Okonwu et al;.…”
Section: Interaction Across Physical Inputs and Crude Oil Pollution Vsupporting
confidence: 58%
“…The interaction between fertilizers and improved seeds showed crops output decrease by 0.102 units in crude oil polluted crop farms. Therefore, crude oil pollution reduced crops output significantly, hence detrimental to crop farms output and production in Rivers State of Nigeria (Achuba, 2006;Aade -Ademilua and Mbamalu, 2008;Dung et al;Okonwu et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations